Risk factors in clinically diagnosed presenile dementia of the Alzheimer type: a case-control study in northern England. Issue 3 (June 1995) - Forster, D P; Newens, A J; Kay, D W; Edwardson, J A
Abstract : STUDY OBJECTIVE--To investigate the relationship between presenile dementia of the Alzheimer type (PDAT) and family history, medical history, cigarette smoking, and exposure to aluminum. DESIGN--A case-control study in which 109 cases of clinically diagnosed PDAT and 109 controls matched for age and sex were compared for exposure to the risk factors. Odds ratios (ORs) were calculated using McNemar's test. SETTING--The northern health region of England. PATIENTS--Cases comprised those under 65 years diagnosed as having dementia by specialist services, who met clinical algorithm criteria for Alzheimer's disease (AD). Cases were confirmed at interview. MAIN RESULTS--Comparing cases with controls, (ORs) significantly greater than unity were obtained when there was a first degree relative with dementia (OR 2.5, 95% confidence interval 1.05, 6.56), any relative with dementia (OR 2.1, 95% CI 1.01, 4.55), and any relative aged less than 65 with dementia (OR 8.0, 95% CI 1.07, 348). Exposure to moderate levels of cigarette smoking (cumulative) was not significant; nor was exposure to aluminum in drinking water, diet, and medicinal sources. CONCLUSION--In this study of modest statistical power, a family history of dementia was confirmed as a risk factor in PDAT. No significant relationship between exposure to aluminium in water supplies, tea, and antacids was found. What is important, however, is the bioavailability of all dietary aluminium, determined by the concentrations of dissolved silicon in water: this requires further investigation.